Research on the impact of artificial intelligence applications on agricultural green development - Shuang Han; Xianmin Sun (Scientific Reports)
Abstract A good ecological environment represents the most inclusive form of people’s well-being, and it is also the greatest advantage and precious asset in rural areas. Therefore, it is of great significance to accelerate the green development of agriculture. Against the backdrop of building livable, industrious, and harmonious countryside, this paper, based on the urban data of the Yangtze River Economic Belt in China from 2011 to 2023, conducts an empirical analysis of the spatial impact and action mechanism of artificial intelligence on the green development of agriculture. The results show that artificial intelligence significantly promotes the green development of agriculture, and this conclusion remains valid after a series of robustness tests. Meanwhile, it is verified that artificial intelligence also has an impact on the green development of agriculture in neighboring areas, indicating the existence of spatial spillover effects. From the perspective of production factors, further research reveals that “the level of human capital” and “the ability of technological innovation” have become important channels through which artificial intelligence drives the green development of agriculture. In addition, by introducing the level of financial support for agriculture, it is found that the positive impact of artificial intelligence features a non-linear decrease in the “marginal effect”. The results of the heterogeneity analysis show that artificial intelligence promotes the green development of agriculture to a greater extent in major grain-producing areas and regions covered by the middle and lower reaches of the Yangtze River, while its promoting effect in the northeastern region has not been prominent. This study not only helps to reveal the driving factors of the green development of agriculture in China in recent years, but also holds great significance for promoting the sustainable and stable green development of agriculture.